Decadal decrease of Antarctic sea ice extent inferred from whaling records revisited on the basis of historical and modern sea ice records - Ackley, Stephen; Wadhams, Peter; Comiso, Josefino C; Worby, Anthony P (Polar Research, 2003)
In previous work, whaling catch positions were used as a proxy record for the position of the Antarctic sea ice edge and mean sea ice extent greater than the present one spanning 2.8° latitude was postulated to have occurred in the pre-1950s period, compared to extents observed since 1973 from microwave satellite imagery. The previous conclusion of an extended northern latitude for ice extent in the earlier epoch applied only to the January (mid-summer) period. For this summer period, however, there are also possible differences between ship and satellite-derived measurements. Our work showed a consistent summer offset (November– December), with the ship-observed ice edge 1 - 1.5° north of the satellitederived ice edge. We further reexamine the use of whale catch as an ice edge proxy where agreement was claimed between the satellite ice edge (1973–1987) and the ship whale catch positions. This examination shows that, while there may be a linear correlation between ice edge position and whale catch data, the slope of the line deviates from unity and the ice edge is also further north in the whale catch data than in the satellite data for most latitudes. We compare the historical (direct) record and modern satellite maps of ice edge position accounting for these differences in ship and satellite observations. This comparison shows that only regional perturbations took place earlier, without significant deviations in the mean ice extents, from the pre-1950s to the post-1970s. This conclusion contradicts that previously stated from the analysis of whale catch data that indicated Antarctic sea ice extent changes were circumpolar rather than regional in nature between the two periods.
Keywords: Sørishavet; Weddellhavet; endringer; havis; historisk; hvalfangere; hvalfangst; iskant; observasjoner; satellite bilder; sjøis

A 1.3-Myr palaeoceanographic record from the continental margin off Dronning Maud Land, Antarctica - Forsberg, Carl Fredrik; Løvlie, Reidar; Jansen, Eystein; Solheim, Anders; Sejrup, Hans Petter; Lie, Hans Erik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
A 12.5 m long core was retrieved from the continental margin off Dronning Maud Land, Antarctica. Magnetostratigraphy, stable isotopes, 14C accelerator mass spectrometer and amino acid analyses indicate a continuous sediment record going back 1.3 Myr. Comparison of CaCO3 results with those from ODP Site 1089 and an index of North Atlantic Deep Water (NADW) influence in surface waters indicate that NADW upwelled along the Antarctic continental margin during the whole of this period. The mid-Pleistocene transition (1.0–0.6 Ma) was accompanied by an apparent decline in the NADW influence, and was followed by extended carbonate dissolution during the interglacials of marine isotope stages (MIS) 13 and 11. Less extensive periods of dissolution occur at the end of the interglacials younger than MIS 11. While interglacial dissolution is characteristic of the Pacific and Indian oceans, the carbon isotopes return to pre-transition values indicative of renewed NADW upwelling. The concentration of ice-rafted debris may reflect changes in the relative rate of interglacial sedimentation. It is speculated that the high ice rafted debris (IRD) concentrations during interglacials younger than 400 kyr may be due to a reduced relative sedimentation rate of other interglacial components whereas the low concentrations during interglacials before the mid-Pleistocene transition may be due to a higher relative sedimentation rate of these.
Keywords: Dronning Maud Land; Weddellhavet; geologi; magnetostratigrafi; oseanografi; paleoklimatologi; paleoseanografi; stabile isotoper

Calcareous dinoflagellate associations and Maastrichtian–Tertiary climatic change in a high-latitude core (ODP Hole 689B, Maud Rise, Weddell Sea) - Hildebrand-Habel, Tania; Streng, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
The distribution of calcareous dinoflagellates has been analysed for the Maastrichtian–Miocene interval of Ocean Drilling Project Hole 689B (Maud Rise, Weddell Sea). The investigation thus represents a primary evaluation of the long-term evolution in high-latitude calcareous dinoflagellate assemblages during the transition from a relatively warm Late Cretaceous to a cold Neogene climate. Major assemblage changes during this interval occurred in characteristic steps: (1) an increase in relative abundance of tangentially structured species – particularly Operculodinella operculata – at the Cretaceous/Tertiary boundary; (2) a diversity decrease and several first and last appearances across the Middle–Late Eocene boundary, possibly attributed to increased climate cooling; (3) a diversity decrease associated with the dominance of Calciodinellum levantinum in the late Early Oligocene; (4) the reappearance and dominance of Pirumella edgarii in the Early Miocene, probably reflecting a warming trend; (5) monogeneric assemblages dominated by Caracomia spp. denoting strong Middle Miocene cooling. The results not only extend the biogeographic ranges of many taxa into the Antarctic region, but also indicate that the evolution of high-latitude calcareous dinoflagellate assemblages parallels the changing environmental conditions in the course of the Cenozoic climate transition. Therefore, calcareous dinoflagellates contribute to our understanding of the biotic effects associated with palaeoenvironmental changes and might possess the potential for reconstructing past conditions. The flora in the core includes one new taxon: Caracomia arctica forma spinosa Hildebrand-Habel and Streng, forma nov. Additionally, two new combinations are proposed: Fuettererella deflandrei (Kamptner, 1956) Hildebrand-Habel and Streng, comb. nov. and Fuettererella flora (Fütterer, 1990) Hildebrand-Habel and Streng, comb. nov.
Keywords: Sørishavet; Weddellhavet; geologi; klimaendringer; paleogeografi; paleoklimatologi; polarområdene

Water mass modification over the continental shelf north of Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Padman, Laurie; Schröder, Michael; Woodgate, Rebecca A.; Jenkins, Adrian; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2003)
We use new data from the southern Weddell Sea continental shelf to describe water mass conversion processes in a formation region for cold and dense precursors of Antarctic Bottom Water. The cruises took place in early 1995, 1998, and 1999, and the time series obtained from moored instruments were up to 30 months in length, starting in 1995. We obtained new bathymetric data that greatly improve our definition of the Ronne Depression, which is now shown to be limited to the southwestern continental shelf and so cannot act as a conduit to northward flow from Ronne Ice Front. Large-scale intrusions of Modified Warm Deep Water (MWDW) onto the continental shelf occur along much of the shelf break, although there is only one location where the MWDW extends as far south as Ronne Ice Front. High-Salinity Shelf Water (HSSW) produced during the winter months dominates the continental shelf in the west. During summer, Ice Shelf Water (ISW) exits the subice cavity on the eastern side of the Ronne Depression, flows northwest along the ice front, and reenters the cavity at the ice front's western limit. During winter the ISW is not observed in the Ronne Depression north of the ice front. The flow of HSSW into the subice cavity via the Ronne Depression is estimated to be 0.9 ± 0.3 Sv. When combined with inflows along the remainder of Ronne Ice Front (reported elsewhere), sufficient heat is transported beneath the ice shelf to power an average basal melt rate of 0.34 ± 0.1 m yr−1.
Keywords: AABW; Sørishavet; Weddellhavet; geofysikk; havstrømmer; isshelf; kontinentalsokkel; oseanografi